THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATION CULTURE ON EMPLOYEE PERFORMANCE AT PT. SURI TANI PEMUKA, SIMALUNGUN REGENCY - Elda Triana Widya; Posma Lumban Raja; Nicholas Marpaung (Transpublika Publisher, 2022)
This study aims to analyze the influence of leadership style and organizational culture on the performance of PT. Suri Tani Pemuka Simalungun Regency. This research uses associative research methods with a quantitative approach. The study population consisted of 752 people, and 88 people were taken as a sample by using purposive sampling techniques. In this study, the data used was primary data obtained from the distribution of questionnaires through Google Form, and secondary data obtained through books, journals, and articles related to this study. The data analysis methods used are validity test, reliability, classical assumption test, multiple linear analysis test, simultaneous test, and determination coefficient test. The findings revealed that leadership style partially has a significant effect on the performance of PT. Suri Tani Pemuka of Simalungun Regency. Meanwhile, organizational culture does not affect the performance of PT. Suri Tani Pemuka of Simalungun Regency. Simultaneously, leadership style and organizational culture have a significant effect on the performance of PT. Suri Tani Pemuka Simalungun Regency 92.7%, while 7.3% was influenced by other factors beyond the study.